2016
DOI: 10.1016/j.ceramint.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Near-zero volume-shrinkage in reactive sintering of porous MgTi2O5 with pseudobrookite-type structure

Abstract: Reactive sintering is an environmentally-friendly processing for porous ceramics. If zero volume-shrinkage in the reactive sintering is realized, the reactive sintering will be more widely applied. Here, we report a new reactive sintering technique to realize near-zero volume-shrinkage (NZVS) in the MgO-TiO2 system. Porous MgTi2O5 pellets have been reactively sintered from LiF-doped hydromagnesite/TiO2 mixed powders with changing TiO2 anatase/rutile compositions. By using the anatase and rutile mixtures as TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides changing the sintering temperature, alternative techniques to control the volume-shrinkage are strongly desired to popularize the reactive sintering. Recently, we have reported that reactively sintered porous MgTi 2O5 from hydromagnesite and TiO2 rutile showed less volume shrinkage than that from hydromagnesite and TiO2 anatase [15]; the volume-shrinkage was well-controlled by changing TiO2 anatase/rutile ratio, enabling even near-zero volume shrinkage [15]. This result has demonstrated that the compositional control of starting polymorphs can be a potential technique to optimize the volume shrinkage in reactive sintering.…”
Section: Introductionmentioning
confidence: 76%
“…4). In the green compact, somewhat large plate-like particles were hydromagnesite and fine spherical particles In our previous report [15], we set up a hypothesis for volume-change behavior in reactive sintering of porous MgTi2O5 from hydromagnesite and TiO2 mixture, where the samples first expanded due to the H2O and CO2 gas emissions by the decomposition of hydromagnesite, and then they shrank by the progress of sintering. Throughout this research, the expansion at step(ii) and step(iii) can be rather attributed to the formation and growth of MgTiO3 and MgTi2O5 particles, respectively.…”
Section: Mechanisms Of Dimensional-change In Reactive Sintering Of Pomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to be able to effectively reduce the size and improve the performance of components, quite a few laboratories place their attention on electronic ceramics. In the field of microwave (MW) dielectrics applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ], electronic ceramics are subject to the following conditions:…”
Section: Introductionmentioning
confidence: 99%